Trust and Retention in Premium Banking Services: Does Switching Costs Matter? - Laksamana, Patria; Wong, David; Kingshott, Russel; Muchtar, Fatimah (Australian and New Zealand Marketing Academy, 2012)
This study sets out to investigate the roles of switching costs between trust and customer retention in premium banking services. Data was collected using a non-probability convenience sample method with 525 usable responses for the data analysis. While trust has been found to have a direct positive impact on retention, switching costs has no influence on the relationship between trust and retention. Implications of the study and the future recommendations are presented and discussed.